A Simple Classroom Teaching Technique To Help Students Understand Michaelis-Menten Kinetics - Runge, Steven W. (American Society for Cell Biology, 2006)
A new, simple classroom technique helps cell biology students understand principles of Michaelis-Menten enzyme kinetics. A student mimics the enzyme and the student's hand represents the enzyme's active site. The catalytic event is the transfer of marbles (substrate molecules) by hand from one plastic container to another. As predicted, increases in marble concentration increase the number of marbles transferred per unit time (initial rate, V(0)) until the turnover number becomes rate limiting and V(0) approaches the maximum velocity (V(max)), as described by the Michaelis-Menten equation. With this demonstration, students visualize an important concept: the turnover number is constant and independent of marble concentration. A student assessment of this exercise showed that it helped students visualize the turnover number and V(max) but not K(m), the marble concentration at which V(0) is one-half V(max). To address the concept of K(m), we use supplemental laboratory and lecture exercises. This exercise with plastic containers and marbles is equally suited to demonstrate the kinetics of carrier-mediated membrane transport. We conclude that this exercise helps students visualize the turnover number and V(max) and gives students important insights into the kinetic parameters used to characterize the catalytic activity of enzymes and membrane transporters.